Enhancing the Skills of Medical Imaging Technology Through Situational Teaching Method for University Students - Miao, Miao; Angsuwotai, Nadda (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2026)
The purpose of this study is 1) to study the effect of the situational teaching method on enhancing the skills of students majoring in medical imaging technology for university students; 2) to compare students' medical imaging technology skills pre-test and post-test; 3) to measure students' attitudes towards the situational teaching method to improve the skills of medical imaging technology for university students. This study adopted the quantitative research method. There were 35 valid questionnaires. This study focuses on second-year students majoring in medical imaging technology at Haibin Medical College. The study covers one class, totaling 35 students. In this research, students undertook medical imaging technology skills learning using the situational teaching method. Pre-test and Post-test assessments were conducted on their attitudes toward situational teaching as a method to enhance medical imaging technology skills. This study finds that 1) The students perceive the situational teaching method as effective and positively impactful; 2) The students achieve skills of medical imaging technology from moderate to very high and has a significant at .01 of pre-test and post-test mean (t-value = 16.8); 3) The students'attitudes towards the situational teaching method to improve the skills of medical imaging technology (X 3.79, S.D. 0.99), all items are high level. This indicates that students hold a positive attitude toward the scenario-based teaching method. This research guides educators in optimizing teaching strategies and refining evaluation methods, thereby contributing positively to the development of high-quality talent in medical imaging technology.